Eksistensi dan Problematika Agama Kaharingan di Kalimantan - Heronimus Heron (Religi: Jurnal Studi Agama-agama, 2021)
Kaharingan is a local religion embraced by the Dayak tribe on the island of Borneo. This belief is believed to have existed before major religions such as Hinduism, Buddhism, or Islam appeared in the Nusantara. Structurally, in 1980 the Indonesian government included Kaharingan as part of Hinduism. In fact, there are many differences between teaching and worship. This was done so that the Dayak tribe could have easy access to the state's civil registration, considering that at that time President Suharto only recognized five official religions. This research uses a literature review method, including reviewing sources from books, news portals, and state legislation texts. The results of this study indicate that the Kaharingan religion has become a deep-rooted identity for the Dayak Tribe. Therefore, their entry into the Hindu religious group certainly creates many problems, both internally and externally. On the other hand, at the organizational level of the Hindu association itself, followers of the Kaharingan religion tend not to get a place. Important positions in Parisada Hindu Dharma Indonesia (PHDI) are dominated by Balinese Hindus. Moreover, now the state has officially recognized that local religious adherents are allowed to register their beliefs in state civil documents. As a result, in 2018, the Kaharingan Religious Council complained to Komnas HAM to fight for it to become an autonomous religion separate from Hinduism.